2014
DOI: 10.3892/or.2014.3505
|View full text |Cite
|
Sign up to set email alerts
|

IGF axis and other factors in HPV-related and HPV-unrelated carcinogenesis (Review)

Abstract: The insulin-like growth factor (IGF) axis promotes the growth of cells, tissues and organs. IGF-1 is mainly produced in the liver but is also secreted from local tissues. In the circulation, IGF-1 is bound to insulin-like binding proteins (IGFBPs), and when released it activates the insulin-like growth factor receptor (IGF-1R). The signal is further transmitted by intracellular signaling pathways leading to gene expression that regulates, among others, cell proliferation and survival. This review presents the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 116 publications
1
20
0
Order By: Relevance
“…On the other hand, it has also been found that HPV infection can escape immune surveillance and response. Thus, research on the mechanisms underlying the latter phenomenon has important significance (Durzynska, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has also been found that HPV infection can escape immune surveillance and response. Thus, research on the mechanisms underlying the latter phenomenon has important significance (Durzynska, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the IGF1 axis is important for proliferation of certain tumor types (reviewed e.g. by Pollak (2008) and Durzyń ska et al (2014)), but it is not known whether insulin effects on tumor progression are mediated via the insulin or the IGF1 receptor. In order to distinguish between insulin actions via IR vs IGF1R we aimed to reduce expression of the IR by lentiviral shRNA KD.…”
Section: Discussionmentioning
confidence: 99%
“…IGFs are multifunctional peptides that play a pivotal role in cell regulation; they consist of IGF‐1 and IGF‐2, with three cell‐membrane receptors and IGF‐binding proteins. These factors can play an important paracrine/autocrine role in promoting tumor growth during tumor progression; however, these roles vary depending on the tissue origin . IGF‐1 may also be a useful biomarker for assessing risk and early diagnosis of precancerous growth in the cervix, and IGF‐2 may be a reliable marker for early diagnosis and the monitoring of therapy efficacy …”
Section: Discussionmentioning
confidence: 99%
“…These factors can play an important paracrine/autocrine role in promoting tumor growth during tumor progression; however, these roles vary depending on the tissue origin. [19][20][21] IGF-1 may also be a useful biomarker for assessing risk and early diagnosis of precancerous growth in the cervix, 22 and IGF-2 may be a reliable marker for early diagnosis and the monitoring of therapy efficacy. 23…”
Section: Hypoglycemiamentioning
confidence: 99%